Rules, Measurements, Geometries, and Underlying Compositions: Graphical/Interpretational Hypotheses Regarding the Holy House of Loreto (diségno, 2020)
This article presents the results of some studies of the Renaissance architectural/sculptural construction constituting the marble surface of the Holy House of Loreto. Detailed representations obtained from a survey using modern digital technologies served as the basis for specific in-depth graphical/analytical investigations of the monument. In particular, this article investigates the following aspects: the proportions of the Corinthian order, an architectural element on which the compositional design of the elevations is based; the proportional relationships among the parts of the capitals of the order compared to two studio drawings for the larger order of Saint Peter’s in Rome deemed to be the work of Bramante; the copresence and correlation in the double rhythm that defines the architectural composition of the faces, echoing the motif of the triumphal arch and the consequent use of an alternating rhythm of two different inter-column spaces, considering as well the relationship with the module identified for the proportions of the order; correspondences with ancient systems of linear measurement in Roman ‘great spans’ and ancient Roman feet presumably adopted to design the marble surface; and the presence of underlying regulating traces, using the golden ratio to arrange the sculpted panels depicting the story of Mary, with particular attention to the low relief of the Annunciation made by Sansovino.
Keywords: exploratory drawing; proportional relationships; module/measurement; systems of measurement; regulating traces